2017
DOI: 10.1039/c7py00484b
|View full text |Cite
|
Sign up to set email alerts
|

Facile green synthesis of isoindigo-based conjugated polymers using aldol polycondensation

Abstract: A green and efficient synthetic protocol suitable for the preparation of isoindigo-based polymer was developed using aldol polymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…Acid‐catalyzed aldol polymerization was used to link the two monomers, and two polymers, LPPV‐1 and LPPV‐2 , with different alkyl chain lengths were synthesized. The aldol polymerization was optimized by tuning the reaction conditions, including the solvent, catalyst, dehydrant, and reaction time (see Table S1 in the Supporting Information) . We found that the products were almost insoluble in common organic solvents if solid dehydrants were added.…”
Section: Figurementioning
confidence: 99%
“…Acid‐catalyzed aldol polymerization was used to link the two monomers, and two polymers, LPPV‐1 and LPPV‐2 , with different alkyl chain lengths were synthesized. The aldol polymerization was optimized by tuning the reaction conditions, including the solvent, catalyst, dehydrant, and reaction time (see Table S1 in the Supporting Information) . We found that the products were almost insoluble in common organic solvents if solid dehydrants were added.…”
Section: Figurementioning
confidence: 99%
“…Previously reported aldol condensation usually adopted p ‐toluene sulfonic acid as catalyst and the polymerization required several hours or even longer time under high temperature (≈140 °C). [ 44,47,48 ] In contrast, the modified aldol condensation in our article requires shorter time (less than 1 h) and much lower temperature (about 70 °C). Moreover, the aldol condensation using TEA as catalysts showed low sensitivity to the reaction solvents.…”
Section: Resultsmentioning
confidence: 88%
“…[ 59,60 ] An alternative environmentally friendly and highly atom economical synthetic strategy is the use of Aldol (poly)condensations between different aromatic units. [ 61,62 ] Nonetheless, both of these synthetic strategies are currently still limited to monomers with specific molecular motifs that render them compatible with the employed reaction conditions. The final consideration for the upscaling of these materials is a shift from batch to flow processes to supply any potential future markets with sufficient quantities of material.…”
Section: Materials Considerationsmentioning
confidence: 99%